2015
DOI: 10.1111/obr.12370
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota‐derived lipopolysaccharide uptake and trafficking to adipose tissue: implications for inflammation and obesity

Abstract: The composition of the gut microbiota and excessive ingestion of high-fat diets (HFD) are considered to be important factors for development of obesity. In this review we describe a coherent mechanism of action for the development of obesity, which involves the composition of gut microbiota, HFD, low-grade inflammation, expression of fat translocase and scavenger receptor CD36, and the scavenger receptor class B type 1 (SR-BI). SR-BI binds to both lipids and lipopolysaccharide (LPS) from Gram-negative bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
156
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(164 citation statements)
references
References 180 publications
(223 reference statements)
5
156
0
3
Order By: Relevance
“…Higher peripheral levels of LPS in obese compared to lean individuals have also been demonstrated [140] . In addition, 4 h after the ingestion of a high-fat diet, obese individuals displayed higher peripheral increments in LPS compared to healthy controls [141] .…”
Section: Obesity and Type 2 Diabetesmentioning
confidence: 94%
“…Higher peripheral levels of LPS in obese compared to lean individuals have also been demonstrated [140] . In addition, 4 h after the ingestion of a high-fat diet, obese individuals displayed higher peripheral increments in LPS compared to healthy controls [141] .…”
Section: Obesity and Type 2 Diabetesmentioning
confidence: 94%
“…They identified a depletion of Parabaceroides distasonis , which has been shown to be anti-inflammatory in the gut and to reduce dextran sodium sulfate-induced inflammatory cytokines and colitis in mice [95]. HFD-fed mice have also been shown to have increased levels of circulating lipopolysaccharide (LPS), a marker of intestinal barrier dysfunction and endotoxemia, which has been shown to promote colorectal cancer development [96]. Another study has suggested that HFD-fed mice have increased colorectal cancer development primarily due to gut dysbiosis associated with obesity.…”
Section: Obesity and Cancermentioning
confidence: 99%
“…Low levels of LPS are physiologically present in the blood of humans and animals. 91 HFD feeding modulates the gut microbiota and increases intestinal permeability, which elevates LPS plasma concentrations. 71,72 In line with these results, LPS also increased miR-155-5p expression in murine pancreatic β-cells in vitro and in vivo.…”
Section: Hyperlipidemia-related Endotoxemia Induces Islet Mir-155-5p mentioning
confidence: 99%